Perspective of System Integration: Research Status and Intervention Measures of Bedtime Procrastination. - Zhang, Siyi (International Journal of Social Sciences and Public Administration, 2024)
Bedtime procrastination has become a common phenomenon, but the dangers of Bedtime procrastination should not be underestimated. Current research in China have been pay attention in bedtime procrastination, but there are still some gaps. This study summarized present study on bedtime procrastination from the perspective of system integration, while conclude intervention pathways, which provided directions for future research and intervention measures.